HUBUNGAN POLIFARMASI DAN POTENSI DRUG-DRUG INTERACTION (DDI) PADA PASIEN PENYAKIT JANTUNG KORONER (PJK) DI RUMAH SAKIT SWASTA BEKASI - Harahap, Nofria Rizki Amalia; Ranti Amanda Putri (Jurnal Riset Kefarmasian Indonesia, 2025)
Patients with coronary heart disease are at high risk of experiencing medication interactions due to the practice of polypharmacy, which involves taking multiple medications. This can lead to negative treatment outcomes. This study aimed to examine the link between polypharmacy and the potential for drug interactions in patients with coronary heart disease. An observational study utilizing a cross-sectional design was carried out using consecutive sampling. The study included 105 patients. The potential for drug interactions was presented in a table based on each patient's medication profile. The relationship between polypharmacy and the potential for drug interactions was analyzed using the chi-square test. The findings revealed that the majority of patients were male (78.1%) and aged 55-64 years (50.48%). The most common potential drug interactions were clopidogrel with atorvastatin (17.54%), followed by atorvastatin-amlodipine (11.7%) and ticagrelor-acetylsalicylic acid (11.11%). The analysis of the relationship between the number of drugs (polypharmacy) and the number of potential drug interactions resulted in a significant value of 0.000 (<0.05) with an odds ratio of 18.5. This means that patients using polypharmacy are 18.5 times more likely to experience drug interactions compared to those using fewer medications.